2001
DOI: 10.1080/146608201753275508
|View full text |Cite
|
Sign up to set email alerts
|

The Rilutek ® (riluzole) Global Early Access Programme: An open-label safety evaluation in the treatment of amyotrophic lateral sclerosis

Abstract: The safety results with this broad population (over 10% of the estimated ALS population worldwide) were consistent with those previously reported from placebo-controlled trials. No increase in adverse events and no unexpected adverse events were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…7 Our findings disagree with the technical data sheet of riluzole 28 that reports oral paresthesia generally in a low percentage of patients (1.6%), reflecting the frequency of SE obtained in clinical trials and observational studies. 2,3,[8][9][10] Furthermore, in our study, the frequencies of liver function abnormalities, asthenia and nausea were relatively low, with respect to other reports. 2,3,8 In 4 out of 45 patients (8.9%), the SEs were responsible for a permanent riluzole interruption.…”
supporting
confidence: 47%
See 2 more Smart Citations
“…7 Our findings disagree with the technical data sheet of riluzole 28 that reports oral paresthesia generally in a low percentage of patients (1.6%), reflecting the frequency of SE obtained in clinical trials and observational studies. 2,3,[8][9][10] Furthermore, in our study, the frequencies of liver function abnormalities, asthenia and nausea were relatively low, with respect to other reports. 2,3,8 In 4 out of 45 patients (8.9%), the SEs were responsible for a permanent riluzole interruption.…”
supporting
confidence: 47%
“…This percentage was lower than the discontinuation rates reported in randomized studies 2,3 and quite similar to that in observational studies. [8][9][10] Although low, this percentage may be remarkable considering that riluzole is one of the few therapies approved for this disease, unlike other diseases as multiple sclerosis in which several drugs of almost equal efficacy are available. 29 Another finding of our study is that the polypharmacy did not influence the adherence to riluzole.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] However, after the clinical trials and the open label studies, clinic and population-based databases led to questions concerning the use of riluzole in the community. These were examined by the King's College Motor Neuron Disease Clinic and the Ireland population-based Motor Neuron Disease Registry.…”
Section: Riluzole Effects In Observational Databasesmentioning
confidence: 98%
“…The long-term safety of riluzole therapy has been established [19,20], including use by elderly patients and those in advanced stages of the disease [21]. According to the Cochrane database, meta-analysis of three controlled, randomized trials with riluzole showed that the mean prolongation of survival in ALS is 2 months [22].…”
Section: Clinical Management and Clinical Trialsmentioning
confidence: 99%